Physiology of integumentary system: Integration from Islamic perspective - Abdul Ghani, Radiah; Hassan, Habibah; Ahmad Roslee, Athirah Nur; Ikmal Hisham, Ahmad Irfan (Springer Nature, 2022)
Human body is one of the most complex creatures which has been mentioned in many divine and modern sources.The skin, or integumentary system is the set of organs forming the outermost layer of human’s body.The scientific research has been progresses tremendously in this area however, there is insufficiency review and description from Islamic perspective. Thus, this paper aims to synthesise available literature on integumentary sciences and relate with Islamic perspective. The roles of integumentary system in fingerprints identification, variation of skin colour, regeneration and replacement of skin in hell fire are explained from the Islamic perspective based on relevant Qur’anic verses and/or the hadith. It is hoped that by viewing and relating Islamic perspective and scientific knowledge it will become a single source of hidayah, the source of truth for this world and the hereafter.